Frontier life: borderlands, settlement & colonial encounters - Adam Matthew Publications
Keywords: _UdeM only

The Making of Modern Law
A collection of digital archives covering classic and contemporary legal traditions in America, Britian, Europe, Latin America, Asia, and other jurisdictions.
Keywords: _no subscription